Exploring system dynamics of complex societal issues through socio-scientific models - Ke, Li; Kirk, Eric; Lesnefsky, Rebecca; Sadler, Troy D. (Frontiers in Education, 2023)
Research on socio-scientific issues (SSI) has revealed that it is critical for learners to develop systematic understanding of the underlying issue. In this paper, we explore how modeling can facilitate students’ systems thinking in the context of SSI. Building on evidence from prior research in promoting systems thinking skills through modeling in scientific contexts, we hypothesize that a similar modeling approach could effectively foster students’ systematic understanding of complex societal issues. In particular, we investigate the affordances of socio-scientific models in promoting students' systems thinking in the context of COVID-19. We examine learners' experiences and reflections concerning three unique epistemic features of socio-scientific models, 1) knowledge representation, 2) knowledge justification, and 3) systems thinking. The findings of this study demonstrate that, due to the epistemic difference from traditional scientific modeling approach, engaging learners in developing socio-scientific models presents unique opportunities and challenges for learners for SSI teaching and learning. It provides evidence that, socio-scientific models can serve as not only an effective but also an equitable tool for addressing this issue.